2023
DOI: 10.1177/03008916231204441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the STK11/KRAS co-mutation on the response to immunotherapy in a real-world pan-cancer cohort

Andrea Olsen,
Alexandra Lebedeva,
Polina Nosova
et al.

Abstract: Introduction: Immune checkpoint inhibitors are highly effective in treating various cancers. We analyzed the significance of the KRAS/STK11 co-mutation in relation to the efficacy of immune checkpoint inhibitors in pan-cancer patient cohort. Methods: We analyzed data from open-access research: MSK-IMPACT (molecular profiling data from patients receiving systemic antitumor therapy) and MSK-TMB (molecular profiling data from patients receiving immune checkpoint inhibitors). In both studies, high throughput seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Another study reported the same results, that is, OS was significantly shorter for patients with STK11 mutation (STK11 Mut 14.2 months vs. STK11 Wt 27.0 months) (28). Among NSCLC patients, the STK11 mutation was associated with a worse outcome for patients receiving systemic antitumor therapy, but not immune checkpoint inhibition therapy (13). Consistent with previous reports, our findings indicated that the presence of STK11 mutation was associated with poor prognosis in NSCLC.…”
Section: B Asupporting
confidence: 90%
See 3 more Smart Citations
“…Another study reported the same results, that is, OS was significantly shorter for patients with STK11 mutation (STK11 Mut 14.2 months vs. STK11 Wt 27.0 months) (28). Among NSCLC patients, the STK11 mutation was associated with a worse outcome for patients receiving systemic antitumor therapy, but not immune checkpoint inhibition therapy (13). Consistent with previous reports, our findings indicated that the presence of STK11 mutation was associated with poor prognosis in NSCLC.…”
Section: B Asupporting
confidence: 90%
“…In preclinical models, STK11 inactivation often led to cancer progression and metastasis and was associated with indolent tumor immune microenvironment, exhibiting as a reduced density of infiltrating cytotoxic CD8 + T lymphocytes, decreased PD-(L)1 expression and a neutrophil-rich tumor microenvironment (7). Loss of STK11 function was identified as a potential feature of malignant tumors in a variety of malignancies, such as cervical cancer (23), meningiomas (24), cholangiocarcinoma (25) and lung cancer (13). STK11 affects tumor cell growth through various important cellular pathways, and gene mutations can affect pathways such as AMPK, STING, and vascular endothelial growth factor, leading to immune suppression and changes in the metabolic environment, which resulted in tumor growth (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations